Contributing factors on students’ willingness to communicate (WTC) - Elis Susanti (Universitas Ahmad Dahlan)
One of the non-linguistics factors which is sometimes out of the teacher’s awareness during the teaching of speaking is how ready or how willing the language learners are to engage in the provided activities in which this psychological condition is then termed as Willingness to Communicate (WTC). To prepare the language learners in order to be more ready or willing is essential to take into account since a fact shows that the high WTC will increase the language learners’ frequency of using the language learned (English) in a communication. This is a descriptive qualitative research which investigated about the students’ WTC in a speaking class consisting of 29 students English Department in STKIP Muhammadiyah Kotabumi. Apart from this, this study also probed what variables influencing their WTC. An observation was done in order to collect the research data and make a conclusion. Due to the collecting data, it was found that students’ WTC is high. Further, some variables such as classroom variables (task type, topic, and interlocutor), individual variables (introversion, self-esteem, and anxiety), and communicative competence are found to contribute on students’ WTC during the speaking activity. Among others, the topic given is as the most influential variable affects students’ WTC. Whereas, it is found that interlocutor variable due to their gender and age does not affect students’ WTC. Hence, English teachers are suggested to give more attention at some variables affecting students’ WTC in order to help the students increase their WTC which leads to their speaking improvement.